Digital leadership in the era of digital transformation: a bibliometric analysis of intellectual structure and thematic evolution (2005–2025) - Inggang Perwangsa Nuralam; Winalda Adelia; Lishapsari Prihatini; Asma; Deby Chinitia Hestiriniah (Har Press Indonesia, 2025)
The accelerating pace of digital transformation has intensified scholarly interest in understanding how leadership practices evolve in technology-driven organizational environments. This study provides a comprehensive bibliometric analysis of digital leadership research by examining 1,325 peer-reviewed articles indexed in the scopus database covering the period 2005–2025. Employing a dual analytical approach combining bibliographic coupling and co-word analysis using vosviewer, the study maps the intellectual structure and thematic evolution of the field. the bibliographic coupling analysis reveals four major research clusters: digital transformation and ai-driven leadership innovation; organizational behavior and workplace leadership dynamics; educational and distributed leadership systems; and digital collaboration and knowledge integration in complex organizational settings. the co-word analysis further identifies three dominant thematic streams: digital transformation and technological leadership ecosystems; agile organizational behavior and leadership practices; and educational leadership and instructional digital innovation. publication trends indicate a strong and sustained growth trajectory, particularly after 2015, reflecting the increasing recognition of digital leadership as a strategic organizational capability in the industry 4.0 era. building on prior fragmented studies in digital leadership and organizational transformation, this research provides a unified, dual-framework bibliometric map that clarifies the intellectual structure, dominant themes, and emerging research directions in the field. the findings contribute to both theory and practice by offering a comprehensive knowledge architecture for understanding how digital leadership enables organizational adaptation, innovation, and performance in digitally intensive environments.